Evolución de la Inversión Extranjera en Ecuador y su Impacto en el PIB - Cueva Galan, Luis Patricio (2024)
All types of investments made by a natural or legal person outside of its country of origin or residence are known as Foreign Investment. FDI is produced horizontally and vertically, For several decades, governments from different economies have focused on creating fiscal policies to facilitate the entry of this type of investment, these are the main promoters of FDI, which enters Latin America, At the end of the 1980s, governments of different countries tried to attract this type of investment through various incentives, although the results were not at the expected levels. The general objective of this research is to analyze the evolution of Foreign Direct Investment (FDI) in Ecuador and its impact on the Gross Domestic Product (GDP). The analysis period is between 2010 and 2020. The methodology integrates a mixed approach by carrying out quantitative and qualitative research of the variables under study first, an Ordinary Least Squares (OLS) econometric model was proposed, but this model had a high level of heteroscedasticity, so a Generalized Least Squares model was proposed to correct the model. Among the main results, it can be established that the two variables have a positive correlation level, although it is low because the volumes of foreign investment have not influenced the generation of new products or services in a greater proportion. The annual FDI entering the country is relatively low compared to the total investment volume since the maximum share it has reached is 6.35% in 2020.